Media Between Being Power and Business - Kocaqi, Elena (Richtmann Publishing, 2012)
Media plays the key role in the relation between politics and electorate. It has the power to make the transparence ofgovernment from one side and from the other side to create the public opinion and to bring in the focus of politic the demands ofelectorate. The role of media in a political system is important and for that reason is called the fourth power that controls the other threepowers. This paper analyses the impact of media in political system and the difficult position of it between being a private business andpower. It analyses how this private business is a public power. It analyses also the public power of media business over the politic, publicand other business.